2019
DOI: 10.1186/s13756-019-0613-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic characterization of clinical isolates belonging to a KPC-2-producing strain of ST15 Klebsiella pneumoniae from a Vietnamese pediatric hospital

Abstract: Background Carbapenem-resistant Klebsiella pneumoniae are becoming increasingly common in hospital settings worldwide and are a source of increased morbidity, mortality and health care costs. The global epidemiology of carbapenem-resistant K. pneumoniae is characterized by different strains distributed geographically, with the strain ST258 being predominant in Europe and USA, and ST11 being most common in East Asia. ST15 is a less frequently occurring strain but has nevertheless been reported w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 20 publications
5
28
1
Order By: Relevance
“…In Africa-Middle East countries , K. pneumoniae and E. coli displayed in vitro susceptibility rates of 96.8% and 100%, respectively to tigecycline [ 14 ]. Other studies from India and outside have reported an increasing prevalence of tigecycline resistance in carbapenem-resistant/MDR K. pneumoniae clinical isolates [ [15] , [16] , [17] ]. A study on isolates from burn wound infections in an Indian tertiary care hospital, reported tigecyline resistance in 9.09% and 11.76% of E. coli and K. pneumoniae , respectively [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Africa-Middle East countries , K. pneumoniae and E. coli displayed in vitro susceptibility rates of 96.8% and 100%, respectively to tigecycline [ 14 ]. Other studies from India and outside have reported an increasing prevalence of tigecycline resistance in carbapenem-resistant/MDR K. pneumoniae clinical isolates [ [15] , [16] , [17] ]. A study on isolates from burn wound infections in an Indian tertiary care hospital, reported tigecyline resistance in 9.09% and 11.76% of E. coli and K. pneumoniae , respectively [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing prevalence of tigecycline- and carbapenem-resistant K. pneumoniae isolates has been reported from China [ 15 ]. In Vietnam, tigecycline susceptibility was observed in only 82% of 57 carbapenem-resistant clinical isolates of K. pneumoniae , belonging to strain ST15 [ 17 ]. The various mechanisms of tigecycline resistance in Enterobacteriaceae include the tetA and OqxAB genes that encode efflux pumps; mutations in the tigecycline target site of ribosomal protein S10 encoded by the rpsJ gene and mutations in the ramR gene, which results in the overexpression of the AcrAB multi-drug pump [ 15 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, various studies have demonstrated the utility of WGS in characterising AMR, transmission routes, and dominant lineages (17)(18)(19). LMICs however remain relatively understudied, with few studies conducted in Vietnamese hospitals (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…A fatal outbreak of carbapenemresistant hypervirulent K. pneumoniae ST11 strains has been reported in a Chinese hospital [17]. The convergence of bla KPC and hypervirulence genes within the same K. pneumoniae ST15 strain has also been identi ed in China and Vietnam [20,23]. Fortunately, none of the ST15 strains detected in this study were positive for hypervirulence genes, and the infection rates of the KPC-producing K. pneumoniae ST15 strains were lower (P = 0.018) than those of the corresponding ST11 strains in our hospital.…”
Section: Discussionmentioning
confidence: 99%